IMMUNOHISTOCHEMICAL ANALYSIS OF THE EXPRESSION OF ALCAM AND ALDH1 MARKERS IN PATIENTS WITH COLORRETAL ADENOCARCINOMA AND ASSOCIATION WITH CLINICOPATHOLOGICAL OUTCOMES - Vasconcelos, Cecilia Neves de (2022)
Background: Colorectal cancer has a high global mortality and tumor markers have emerged as diagnostic, management and prognostic indicators. New markers are being studied. Objective: To verify if there is a correlation between the immunohistochemical expression of ALCAM and ALDH1 proteins in colorectal adenocarcinoma tissue with epidemiological and clinicopathological characteristics, in particular their impact on disease progression and death. Method: Observational, single-center, analytical, retrospective study, through the investigation of patients undergoing surgical resection for colorectal cancer. 122 patients were evaluated. Regarding progression, it was shown that in individuals with positive ALCAM (n=40), 14/40 (35%) had progression, and for positive ALDH (n=54), 22/54 (40.7%). For death, the analysis of ALCAM positive (n=40), 24/40 (60%) died, and ALDH1 positive (n=54), 33/54 (61.1%). Conclusion: The immunohistochemical expression of ALCAM and ALDH1 markers was not associated with disease progression and death; it was also not possible to observe a correspondence relationship with the evaluated markers.